High-coercivity Sm(Fe, V, Ti)12 bulk magnets. (January 2021) - Saito, Tetsuji; Watanabe, Fumiya; Nishio-Hamane, Daisuke
Graphical abstract: Highlights: The Sm(Fe, V, Ti)12 magnets phase were produced by the spark plasma sintering method. The Sm(Fe, Ti, V)12 magnets consisted of the Sm(Fe, V, Ti)12 phase. The SmFe10 V1.5 Ti0.5 magnets exhibited a high coercivity of 0.74 MAm -1 . Abstract: Sm(Fe, V, Ti)12 melt-spun ribbons were consolidated into bulk magnets. The resultant Sm(Fe, Ti, V)12 magnets consisted of the Sm(Fe, V, Ti)12 phase. The magnetic properties of the Sm(Fe, V, Ti)12 magnets were strongly dependent on the composition and consolidating temperature. The highest coercivity of 0.74 MAm -1 was achieved in the SmFe10 V1.5 Ti0.5 magnet sintered at 973 K, which consisted of fine equiaxed grains of the Sm(Fe, V, Ti)12 phase.